Legal Consequences of Bankruptcy for Creditors Holding Mortgage Rights and Execution Parate - Rizalni Kurniawan, Aan; Santiago, Faisal; Isretno Israhadi, Evita (Jurnal Indonesia Sosial Sains, 2023)
The right of the separatist creditor as the holder of the mortgage right is clearly regulated by Law Number 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land (henceforth referred to as UUHT) Article 20 paragraph (1). In particular, the effect of bankruptcy on mortgage rights appears with the existence of Article 56 paragraph (1) UUK which states that the execution right of a separatist creditor holding mortgage rights against mortgage rights that are in the control of creditors is suspended for a maximum period of 90 days (stay period). The rights of the mortgage holder that have been protected by Article 20 paragraph (1) and Article 21 UUHT are no longer protected if the debtor is declared bankrupt because Article 56 paragraph (1) UUK (stay period) applies which suspends the execution of the mortgage holder for 90 days.